Anabolic Resistance of Muscle Protein Turnover Comes in Various Shapes and Sizes - Paulussen, Kevin J. M.; McKenna, Colleen F.; Beals, Joseph W.; Wilund, Kenneth R.; Salvador, Amadeo F.; Burd, Nicholas A. (Frontiers in Nutrition, 2021)
Anabolic resistance is defined by a blunted stimulation of muscle protein synthesis rates (MPS) to common anabolic stimuli to skeletal muscle tissue such as dietary protein and exercise. Generally, MPS is the target of most exercise and feeding interventions as muscle protein breakdown rates seem to be less responsive to these stimuli. Ultimately, the blunted responsiveness of MPS to dietary protein and exercise underpins the loss of the amount and quality of skeletal muscle mass leading to decrements in physical performance in these populations. The increase of both habitual physical activity (including structured exercise that targets general fitness characteristics) and protein dense food ingestion are frontline strategies utilized to support muscle mass, performance and health. In this paper, we discuss anabolic resistance as a common denominator underpinning muscle mass loss with aging, obesity, and other disease-states. Namely, we discuss that anabolic resistance exists as a dimmer switch, capable of varying from higher to lower levels of resistance, to the main anabolic stimuli of feeding and exercise depending on the population. Moreover, we review the evidence whether increased physical activity and targeted exercise can be leveraged to restore the sensitivity of skeletal muscle tissue to dietary amino acids regardless of the population.